Comparison of endoscopic visibility and miss rate for early gastric cancers after Helicobacter pylori eradication with white‐light imaging versus linked color imaging. Issue 5 (26th December 2019) - Kitagawa, Yoshiyasu; Suzuki, Takuto; Nankinzan, Rino; Ishigaki, Asuka; Furukawa, Kiyoto; Sugita, Osamu; Hara, Taro; Yamaguchi, Taketo
Abstract : Background and Aim: We aimed to investigate whether linked color imaging (LCI) improves endoscopic visibility of early gastric cancers (EGC) after Helicobacter pylori eradication, which are often difficult to detect, and reduces the miss rate when compared with white‐light imaging (WLI). Methods: The visibility study used two images, one each with WLI and LCI, from 84 consecutive EGC after H. pylori eradication. Endoscopic visibility was evaluated using a visibility score and color difference (CD) value. To analyze miss rates, we studied a library of recorded videos using both WLI and LCI for 70 other consecutive patients after H. pylori eradication, among whom 19 had EGC. Endoscopic screening was done using the same protocol to map the entire stomach. Six endoscopists reviewed the videos in a randomized order. Miss rates of EGC were compared among the modalities. Results: Mean [(±standard deviation) visibility scores with LCI were significantly higher than those with WLI (3.19 ± 0.84 vs 2.52 ± 0.98, P  < 0.001), as were mean CD values (26.3 ± 9.1 vs 13.6 ± 6.3, P  < 0.001). Miss rates of the six endoscopists were significantly lower with LCI than with WLI (30.7% vs 64.9%, P  < 0.001). Both expert and trainee endoscopists had significantly better results with LCI than with WLI. Conclusions: Linked color imaging significantly improved the visibility of EGC after H. pylori eradication compared with WLI using both subjective and objective criteria. Furthermore, LCI significantly reduced miss rates of these lesions compared with WLI.